Hydro-thermal power market equilibrium with price-making hydropower producers. (1st December 2018) - Löschenbrand, Markus; Wei, Wei; Liu, Feng
Abstract: This paper formulates an electricity market dominated by price-making hydro-thermal generation. Generation companies optimize their unit commitment, scheduling and bidding decisions simultaneously as a Mixed Integer Programming problem and participate in a market under quantity competition, giving rise to a discontinuous Nash-Cournot game. Both hydropower and thermal units are considered as price-makers. The market equilibrium under uncertainty is computed via time stage decomposition and nesting of a Continuous Nash game into the original Discontinuous Nash game that can be solved via a search algorithm. To highlight applicability of the proposed framework, a case study on the Scandinavian power market is designed and suggests positive welfare effects of large scale storage, whereas the implications on scheduling of conventional units are subsequently discussed. Reformulation allows computationally efficient scaling of the problem and possible extensions to allow large scale applications are discussed. Highlights: A stochastic game model for hydro-thermal power market with price-maker hydropower producers. A computational method to locate all Nash equilibria for the proposed non-convex game model with integer variables. A decomposition approach to cope with periodical inflows.